Pengaruh Efektivitas Penggunaan, Kepercayaan,Pemanfaatan, dan Keahlian pada Teknologi SistemInformasi Manajemen Daerah (SIMDA) Terhadap KinerjaIndividu Pegawai(Studi Empiris pada Satuan Kerja Perangkat Daerah Kota Surakarta) - Khairunnisa, Eviana; Trisnawati, Ak, M.Si, Ph.D, Dra. Rina Trisnawati, Ak, M.Si, Ph.D (2016)
This study aimed to examine the influence of using effectivity, trust, utility, and technology expertise of SIMDA on individual performance. This study used primary data collected by a questionnaire. The population of this research are the entire employees of SKPD Surakarta City. The sample collection technology has been done by using convinience. The sample was 42 SKPD in Surakarta City. Based on the results of multiple regression analysis shows that the effectiveness variable of using and the utilization of technology SIMDA not affect the individual performance of the employees. While the trust variable and the expertise of SIMDA technology user have infulence to the performance of the individual employees.